Sustaining Tourism during War: A Case of Russia and Ukraine - Neelu Neelu; Mukesh Kumar (ASEAN Journal on Hospitality and Tourism, 2023)
This study investigates the underlying motivation for visiting Russia and Ukraine based on which policymakers can frame policies and campaigns around tourism in these war-ravaged countries. Finding ways to promote and sustain tourism in such destinations can immensely contribute to the economy of these nations.  The study was conducted by collecting both primary and secondary data. For secondary data, online news sources and Google Trends were employed; for primary data, responses were collected from 207 Indian subjects through an online questionnaire for eliciting responses from a diverse set of subjects a broader reach. The results indicated a clear impact on rising interest of tourists in these countries despite the popular assumption that war might deter tourists from entering such destinations. The subjects admitted that the war ignited their curiosity in Ukraine's people, culture and destinations. This research is the first of its kind, which explores the motivation of tourists to travel to Russia and Ukraine while they are still at war and the ways in which countries can sustain tourism during the period of war.